PEMANFAATAN LIMBAH SERAT INDUSTRI TEPUNG SAGU AREN SEBAGAI BAHAN BAKU PEMBUATAN KERTAS (PULP) DENGAN PROSES DELIGNIFIKASI - -, Purnawan (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
There are several home industries in sago aren processes center in Daleman, Tulung, Klaten, Central Java, produce sago aren flour product (soun) an average of 200 tons/year, these home industries produce waste by product of sago fibre. The process of pulp from sago fibre is done by two steps of the process, step one is with using nitric acid (HNO3) and second process with soda coustic (NaOH). The process is conducted in three neck flask equipped with a stirrer, and cooller. The temperature is kept constant. Delignification process of sago aren fibre was carried and by two steps. Firstly 10 grams of sago fiber adds by 400 ml of HNO3 7.5%. Secondly the product of step one adds by 400 mL of NaOH 7.5%, while the condition of both steps one kept on temperature of Â±103 0C, and the stirring speed of 400 rpm, obtained relatively good condition by using NaOH concentrations of 7.5% and 1.5 hours of processing time. In these conditions the percentage of product cellulose results obtained is 33.41%, with the permanganate numbers of 1.28, the concentration of Î± cellulose 95.74%.